Changes in self-reported health and quality of life in octogenarian patients one month after transcatheter aortic valve implantation. (January 2017) - Olsen, Siv JS; Fridlund, Bengt; Eide, Leslie SP; Hufthammer, Karl O; Kuiper, Karel KJ; Nordrehaug, Jan E; Skaar, Elisabeth; Norekvål, Tone M; ,
Background: In addition to favourable results regarding mortality and morbidity it is important to identify the impact transcatheter aortic valve implantation (TAVI) has on patients' quality of life. Aims: The aims were: (i) to describe clinical characteristics, self-reported health and quality of life in octogenarians before TAVI intervention; (ii) to determine changes in self-reported health and quality of life one month after TAVI; and (iii) to establish the clinical importance of the findings. Methods: A prospective cohort study was conducted on consecutively enrolled octogenarians with severe aortic stenosis undergoing TAVI ( N = 65). Self-reported health and quality of life were recorded at baseline and one month later using two global questions from the World Health Organization Quality of Life Instrument Abbreviated (WHOQOL-BREF), the generic Short Form Health 12 and the disease-specific Minnesota Living with Heart Failure Questionnaire. Results: One month after TAVI, WHOQOL-BREF showed that self-reported health improved moderately ( p < 0.001), while quality of life improved slightly, but not statistically significantly ( p = 0.06). There were changes in all Short Form Health 12 domains, except social functioning and role emotional. The estimated changes were 3.6 to 5.8 with large confidence intervals. The Physical Component Summary increased statistically significantly from baseline to 30 days (30.6–34.7; p = 0.02), but the Mental Component Summary did not (46.9–50.0; p = 0.13). Conclusion: Despite being an advanced treatment performed in a high risk population, TAVI in octogenarians improves short-term self-reported global health and generic physical health and quality of life. These patient-reported outcomes have importance, particularly in this age group.